Solubility and thermodynamics of lamotrigine in ternary mixtures of ionic liquids ([OMIm][Br] + [HMIm][Br] + water) at different temperatures - Barzegar-Jalali, Mohammad; Jouyban, Abolghasem; Martinez, Fleming; Shekaari, Hemayat; Mirheydari, Seyyedeh Narjes (Chinese journal of chemical engineering, 2020)
Experimental mole fraction solubility of lamotrigine (LTG) in ternary aqueous mixtures of two ionic liquids (ILs), 1-hexyl and 1-octyl-3-methylimidazolium bromide, [HMIm][Br] and [OMIm][Br] were reported at several temperatures T = (293.15 to 313.15) K. The van't Hoff and (Jouyban-Acree-van't Hoff, E-Jouyban-Acree-van't Hoff, e-NRTL, UNIQUAC and Wilson) models were used to correlate the solubility data. The comparison of the models with temperature and solvent composition dependencies shows that the Wilson model has the minimum ARD which are relatively close to those obtained from Jouyban-Acree-van't Hoff and E-Jouyban-Acree-van't Hoff models and maximum ARD belonged to the UNIQUAC model. The order of ARDs for these models is: Wilson < Jouyban-Acree-van't Hoff, E-Jouyban-Acree-van't Hoff < e-NRTL < UNIQUAC. Moreover, the apparent thermodynamic functions, Gibbs free energy, enthalpy and entropy of dissolution and mixing were calculated based on the van't Hoff and Gibbs free energy equations. The strong LTG-ILs interactions and enthalpic contribution of the dissolution process resulted from the calculated thermodynamic functions. [Display omitted]